2014
DOI: 10.17129/botsci.94
|View full text |Cite
|
Sign up to set email alerts
|

Estructura de un bosque natural perturbado de Pinus tropicalis Morelet en Galalón, Cuba

Abstract: Resumen: Los bosques naturales de Pinus tropicalis Morelet en Cuba han sido alterados por prácticas inadecuadas de aprovechamiento forestal. Esta investigación tiene el objetivo de caracterizar la estructura de un bosque perturbado de Pinus tropicalis en Galalón, Pinar del Río. Para ello se realizó un inventario fl orístico, se determinaron los índices de valor de importancia ecológica y de importancia ecológica ampliado. Se calculó la diversidad alfa mediante el recíproco del índice de Simpson (1/D) y el índi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
0
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
3
0
0
2
Order By: Relevance
“…Site six was presented as the most diverse area, expressed through the Shannon index, with higher equitability (Equity) and lower dominance (Simpson). These results correspond with what was reported by Valdés et al (2014) and García et al (2016) for pine forests, attributing the low diversity to the influence of anthropization and ecosystem type. According to Alvis Gordo (2009), natural tropical forests are heterogeneous and are made up of a high diversity of species, with different successional ages: sapling, latizal and fustal.…”
Section: Resultssupporting
confidence: 92%
“…Site six was presented as the most diverse area, expressed through the Shannon index, with higher equitability (Equity) and lower dominance (Simpson). These results correspond with what was reported by Valdés et al (2014) and García et al (2016) for pine forests, attributing the low diversity to the influence of anthropization and ecosystem type. According to Alvis Gordo (2009), natural tropical forests are heterogeneous and are made up of a high diversity of species, with different successional ages: sapling, latizal and fustal.…”
Section: Resultssupporting
confidence: 92%
“… Benítez-Malvido and Martínez-Ramos (2003) indicated that vegetation fragmentation allows for greater species richness, because it creates more distinct habitats to occupy. These results correspond to those obtained by Valdés-Sáenz et al. (2014) in forest areas with different levels of disturbance, and Patiño et al.…”
Section: Discussionsupporting
confidence: 91%
“…The pioneer species of secondary forests that are typical of ecological succession can be considered as indicative of the changes that have occurred in the forest areas of the upper Puyo River micro-basin. This corresponds to what was stated by Valdés-Sáenz et al. (2014) , namely that the IVI values may be a reflection of the anthropization that some species of commercial interest are subject to.…”
Section: Discussionsupporting
confidence: 80%
“…En este escenario es necesario promover acciones de restauración que permitan la rehabilitación de los sitios más perturbados a partir de grupos núcleos de familias botánicas para cada condición local. Estos resultados se corresponden con lo descrito por Valdés-Sáenz et al (2014), Gutiérrez y Becerra (2018) y Vega (2020), quienes refieren que las perturbaciones antrópicas alteran sensiblemente los patrones de estructura y composición en las comunidades vegetales.…”
Section: Discussionunclassified